THE EFFECT OF WORKING CAPITAL ON THE PROFITABILITY OF PALM OIL PLANTATION COMPANIES - Tania Prafitri; Dwi Rachmina; Tubagus Nur Ahmad Maulana (School of Business, IPB University (SB-IPB), 2017)
Management decisions related to working capital are based on the management of short-term assets and liabilities, aiming to ensure that the company is able to maintain the operations and have sufficient cash flows to finance short-term debt maturities and operational costs, as well as to improve the profitability of the company. The objective of this study is to examine the effect of working capital management on company profitability. Working capital is considered to be an important issue in financial management and have an effect on liquidity as well as on the company profitability. In addition, optimized working capital management contributes greatly to the achievement of company objectives. The secondary data were taken from the annual reports of 6 oil palm plantation companies registered in the Indonesia Stock Exchange (IDX) during the year 2009-2015. Profitability as a dependent variable was measured by return on investment (ROI). Cash conversion cycle (CCC), current ratio (CR), financial debt ratio (FDR), and fixed financial asset ratio (FFAR) are independent variables. The analytical model used in this study was panel regression by using Fixed Effect Model. The results showed that there is a negative effect of working capital on profitability. Profitability will increase as cash cycle conversion cycle decreases. This is because companies with short cash conversion cycle are able to collect the cash needed for the company's day-to-day operations.Keywords: working capital, cash conversion cycle, current ratio, debt ratio, fixed assets ratio. profitabilityABSTRAKKeputusan manajemen yang berkaitan dengan modal kerja didasari oleh cara pengelolaan antara aset dan kewajiban jangka pendek, hal ini bertujuan untuk memastikan bahwa perusahaan mampu untuk melanjutkan kegiatan operasional dan memiliki arus kas yang cukup untuk membiayai hutang jangka pendek yang jatuh tempo dan biaya kegiatan operasional, serta untuk meningkatkan profitabilitas perusahaan. Tujuan dari makalah ini adalah menganalisis pengaruh manajemen modal kerja terhadap profitabilitas perusahaan. Modal kerja dianggap sebagai masalah yang penting dalam manajemen keuangan dan memiliki efek pada likuiditas serta pada profitabilitas perusahaan. Selain itu, manajemen modal kerja yang optimal memberikan kontribusi yang besar dalam pencapaian tujuan perusahaan. Penulis menggunakan data sekunder yang bersumber dari laporan tahunan 6 perusahaan perkebunan kelapa sawit yang terdaftar di Bursa Efek Indonesia (BEI) selama tahun 2009–2015. Profitabilitas sebagai variabel dependen diukur dengan return on investment (ROI).Cash conversion cycle (CCC), current ratio (CR), financial debt ratio (FDR), dan fixed financial asset ratio (FFAR) merupakan variabel independen. Model analisis yang digunakan adalah model regresi panel menggunakan Fixed Effect Model. Hasil penelitian menunjukkan bahwa ada pengaruh negatif dari modal kerja terhadap profitabilitas. Profitabilitas akan bertambah saat waktu siklus konversi kas berkurang. Hal ini dikarenakan perusahaan yang memiliki waktu siklus konversi kas yang pendek mampu mengumpulkan kas yang diperlukan untuk operasional sehari-hari perusahaan.Kata kunci: modal kerja, siklus konversi kas, rasio lancar, rasio hutang, rasio aktiva tetap profitabilitas